Strategic operations management in modern industrial business systems - Rintala, Onni Erkki Juhani (My University, 2024)
Strategic operations management is considered as the integration of strategic and operational decision-making aiming to maximize value generation capabilities, operational excellence and business competitiveness with the available resources and competencies. The role of strategic operations management, along with the utilization of data-driven decision-making through information technologies, has increased its importance in the modern, complex and dynamic business environment. The role of strategic operations management is crucial in value chain performance as an effective demand chain creates value from which the company extracts its profits through an efficient supply chain. Strategic operations management is about putting strategy into practice by enhancing the fit of operations to competitive priorities determined in competition strategy and strategic alignment among operations to achieve sustainable competitive advantage. As a result of successful strategic operations management is a value chain that integrates and synchronizes supply chain and demand chain operations providing superior business competitiveness. This thesis work delves into strategic operations management in modern industrial business systems to understand its role and value in the current complex, dynamic and competitive business landscape with unpredictable disruptions and risk factors. The purpose of this thesis is to develop a holistic theoretic understanding of strategic operations management, its role and observe its applications in the form of different operating models. A comprehensive review of strategic management in the context of operations gives insights on how the design of operations system can support and enhance business competitiveness and performance. The thesis is conducted as a literature review in which 112 pieces of business literature work have been reviewed. The thesis focuses on strategic level decisions and aspects of competitiveness, sustainability and technology. The thesis includes a number of reasons why strategic operations management has a high importance in the field of modern manufacturing industries and why it should be considered with care in order to achieve sustainable competitive advantage. The thesis highlights the effects of successful strategic operations management on the quest for business competitiveness through a combination of effectiveness and efficiency. This thesis focuses on industrial manufacturing business perspective with a strategic scope and concentrates on modern business systems from an internal company perspective rather than further analyzing the external business environment.
Keywords: agile methods; operations models; strategic planning; value chains; lean manufacturing; modularity; competitive advantage; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; fi=Energia- ja informaatiotekniikan ohjelma|en=Degree Programme in Energy Technology and Information Technology|